Diversity of Soil Macrofauna in Various Ecosystems in Tahura Sultan Thaha Syaifuddin Jambi - Haneda, Noor Farikhah; Anggarawati, Sri Hastuti; Arsita, Lika (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
Soil macrofauna is one of the important components of soil organisms that play a role in maintaining soil fertility through the breakdown of organic matter, nutrient distribution, and their activities can increase aeration and water infiltration. This study aims to calculate and compare the diversity, abundance, richness, evenness and similarity of soil macrofauna species in four different forest stands, namely secondary forests, oil palm plantations, ironwood stands and rubber stands in the Sultan Thaha Syaifuddin Grand Forest Park, Batang Hari Regency, Jambi Province. Direct sampling method using handsorting. Samples that have been taken are put into a sample bottle containing 70% alcohol. The identification of insect samples refers to the insect identification book in the Forest Entomology Laboratory of the Silviculture Department, Faculty of Forestry and Environment, Bogor Agricultural University. The highest species diversity is found in secondary forests, while the lowest species diversity is found in oil palm plantations. Keywords: diversity, grand forest park, identification, soil macrofauna